2023
DOI: 10.31933/dijemss.v4i4.1734
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Affect the Quality Of Vocational Education Graduates in the 4.0 Era: Job Readiness, Skills and Digital Services

Abstract: Vocational education is an education that provides technical skills, knowledge and abilities needed by the workforce in various industrial sectors, but currently there are many graduates who are not accepted to work in the industrial sector, including because the graduates do not have the quality that adequate according to industry standards.  The purpose of this study is to find out several factors that affect the quality of graduates. This research method is a literature review taken from several digital sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This value aim analysis hypothesis study. Coefficient determination (R 2 ) measure model capabilities explained other variables with endogenous variables (Irfansyah et al, 2023). Classification coefficient correlation: R 2 > 0.607: correlation good; 0.330 < R 2 < 0.670: correlation sufficient and 0.190< R 2 < 0.330: correlation weak,.…”
Section: Resultsmentioning
confidence: 99%
“…This value aim analysis hypothesis study. Coefficient determination (R 2 ) measure model capabilities explained other variables with endogenous variables (Irfansyah et al, 2023). Classification coefficient correlation: R 2 > 0.607: correlation good; 0.330 < R 2 < 0.670: correlation sufficient and 0.190< R 2 < 0.330: correlation weak,.…”
Section: Resultsmentioning
confidence: 99%
“…In light of this, Wafa et al, (2020) found that both graduates and employees feel unprepared for the digital world of work, highlighting the need for individuals to develop competencies beyond their qualifications to succeed in the unpredictable and rapidly evolving digital-era work world where jobs and occupational pathways have become blurred and uncertain. Competencies such as adaptability and problem solving, will ensure that graduates are ready to work and meet the requirements of the industry (Irfransyah et al, 2023). To further expand the understanding of individuals' awareness of the digital world of work, this study presents findings on higher education students' perceptions of their readiness and competency for the world of work, and the extent to which these attributes predict their digital work world awareness.…”
Section: Introductionmentioning
confidence: 99%